Actitudes y recursos didácticos en la comprensión de textos en inglés en estudiantes del cuarto grado de secundaria en instituciones educativas estatales, distrito de Fernando Lores 2019 - Marin Arirama, Cheryl Jhossely (2021)
The main objective of this research was to explain the influence of the attitude and didactic resources in the comprehension of texts in English in fourth grade high school students in the state educational institutions of Fernando Lores District, 2019; being the explicative type study with a non-experimental, cross-sectional design. The study population was made up of 137 students from the fourth grade of secondary school and the sample unit was the same, applying the census method for convenience. The data was collected through questionnaires and a written test; the instruments were previously validated by expert judgment. The results show that there is an influence of the variables attitude and pedagogical resources in the comprehension of texts in English in the student’s subject to the research, observing that the attitude is adequate in those who show excellent, good and regular reading comprehension and these same students mention that the pedagogical resources used were good. It should be noted that conventional pedagogical resources influenced more than avant-garde ones. To contrast the main hypothesis considered in the study, we proceeded to check the specific hypotheses with the Kendall Taub test statistic, after having carried them out, both are demonstrated, so the main hypothesis of the research is demonstrated: The attitude and the teaching resources significantly influence the comprehension of texts in English in fourth grade high school students in the state educational institutions of Fernando Lores District, 2019.